INTENSITAS PEMBELIAN ITEM VIRTUAL PEMAIN MOBILE LEGENDS DI KARAWANG: TINJAUAN SISTEM PEMBAYARAN DIGITAL DAN LITERASI KEUANGAN - Jimi; Suroso; Dwi Epty Hidayati (STIE Mahardhika, 2026)
Minithesis of article. No more than 250 words. Contains of aim of research, method, result and discussion. No references and endnote or bodynote The purpose of this study is to assess how frequently Mobile Legends gamers in Karawang Regency purchase virtual items in relation to digital payment methods and financial literacy. This study uses an associative causal strategy in a quantitative manner. Purposive sampling and the chochran formula were used to establish the sample size, which came out to 196 respondents. An online questionnaire with a Likert scale from 1 to 5 was used to collect the data, and multiple linear regression analysis was carried out with the aid of SPSS software. The results show that the frequency of virtual item purchases is positively and significantly impacted by both digital payment systems and financial literacy. Concurrently, both factors also shown a substantial relationship, with a coefficient of determination (R Square) of 57%, suggesting that players' comprehension of financial management and the simplicity of making digital transactions have an impact on the frequency of purchases.